President’s Message - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2004)
As the season changes to winter, and this year is followed by a new year, I begin to reflect on the last year. ORNAC has had many changes in 2004 and our progress seems to be unstoppable.